A Case Report of Misdiagnosed Breast Implant-associated Anaplastic Large Cell Lymphoma with Lymphatic Extension. Issue 11 (November 2021) - Maglic, Dino; Moss, Whitney; Pires, Giovanna; Agarwal, Archana; Matsen, Cindy; Kwok, Alvin
Abstract : Summary: Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a rare peripheral T-cell lymphoma associated with textured implants and usually presents as a late-onset periprosthetic seroma. We present a 70-year-old woman with a history of left breast invasive ductal carcinoma treated with mastectomy and textured implant-based reconstruction, and subsequent adjuvant chemotherapy due to lymphovascular extension. Eleven years following her reconstruction, the patient developed a periprosthetic seroma. Fine needle aspiration and partial capsulectomy were performed, but appropriate pathologic evaluation was not initially submitted. She then presented with lymphadenopathy, which was biopsied and revealed BIA-ALCL within an axillary lymph node. Despite implant explantation, complete capsulectomy, axillary lymph node dissection, and excision of groin lymphadenopathy, no evidence of primary ALCL was appreciated. This initially misdiagnosed case demonstrates the importance of following the National Comprehensive Cancer Network guidelines when a patient presents with late onset breast periprosthetic effusions.